An investigation of financial inclusion of muslims in selected muslim populated states in India - Rafiq, Mansha (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
Indian banking sector has grown tremendously over the years in terms of performance and complexity. In spite of this progress, a large number of people have limited or zero access to the financial services. In the modern era, financial institutions serve as facilitators of economic progress and advancement. It is, therefore, necessary that people have equal access to these financial institutions and the services they offer especially in emerging economies like India. Financial Inclusion thus emerges as a necessity for it is equally beneficial to the banks as well as to the unserved population vis-a-vis the provision of new business avenues for the former and financial services for the latter. The concern based on which this study is derived is the increasing financial exclusion among Indian population generally and Muslims in India specifically. Empirical and theoretical evidences exist demonstrate that there are many possible causes of this increasing exclusion among the Muslims. In this study, we used panel data covering 14 Muslim populated Indian regions (13 states and 1 union territory) over a period of eight years, from 2009 to 2016, to assess the factors influencing financial inclusion in terms of credit and deposit penetration. By employing an explicit econometric model for panel data in statistical software STATA, it is found that distinct state-effect is prevalent among the Indian states. Further, the number of banking offices, per capita net state domestic product, outstanding liabilities, social sector expenditure, number of employees and interest payments are some significant factors that influence the credit and deposit penetration. An increasing trend has been seen when it comes to analysing the problem of exclusion and numerous efforts have been made by the Indian government to demonstrate its compliance with global practices to tackle exclusion. This is in particular relation to designing various policies and schemes as a strategy to stem the negative tide of exclusion. Regardless of these efforts, the Muslim population in India seems to have not shown much progress and inclination towards attaining formal financial services because of their faith as these facilities deal with interest which is strictly prohibited in Islam. Under these circumstances, the introduction of interest-free banking facilities has been suggested by various scholars and studies in the past to culminate this crisis. Motivated by the gap, the study further aims at investigating the potential of Islamic banking in the highest Muslim populated state of India i.e., Jammu and Kashmir by ascertaining the important factors that are essential for introducing Islamic banking in the state. To meet this objective, the survey data is collected from IBK and upon extracting the factors through Exploratory Factor Analysis (EFA), regression analysis is performed. The results suggest that factors that play a role for adopting Islamic banking and finance in the state of Jammu &Kashmir are features, awareness and support towards Islamic banking and finance. Recommendations based on research findings such as opening new branches in rural areas, increasing spending on social sector and introducing interest-free banking modules in Muslim concentrated were offered.